(untitled) (Nordic Journal of African Studies, 2003)
This article examines and analyses the language of dirges among the Kpe (or Bakweri), a homogenous ethnic group of semi-Bantu stock in the Southwestern region of Cameroon. By so doing, it exposes the fascinating language variety of the Kpe dirge form as poetry. The article is of the view that the structure of the dirges, their chant and antiphonal form, the figurative language employed by the performers (that includes lyrical repetition, personification, symbolism, imagery, apt metaphors, and allusions) constitutes some of the essential components that are utilized in the realization of this funeral poetry. The article also highlights the use of a free rhythm (that is most often enhanced by the collaboration of a lead singer and chorus) in the performances of Kpe dirges. This rhythm is articulated by dance, the accompaniment of drumming, ringing of bells, and the playing of a host of assorted musical instruments. This employment of rhythm demonstrates how the individual performer has the flexibility to treat the themes in her own way and, in so doing, expressing her emotions in the words and melodies she chooses. The vivid pictures that are conjured from the performers’ imagination as they perform these funeral songs generate emotive feelings that suit the mournful atmosphere of Kpe funerals.